Magnetic Phase Separation and Magnetic Moment Alignment in Ordered Alloys FE65Al35−xMx (Mx = Ga, B; x = 0; 5 at.%) - E. V. Voronina; A. K. Arzhnikov; A. I. Chumakov; N. I. Chistyakova; A. G. Ivanova; A. V. Pyataev; A. V. Korolev (Advances in Condensed Matter Physics)
The structure and the magnetic state of ordered Fe65Al35-xMx (Mx = Ga, B; x = 0; 5 at.%) alloys are investigated using X-ray diffraction, Mössbauer spectroscopy, and magnetic measurements. The behavior of the magnetic characteristics and Mössbauer spectra of the binary alloy Fe65Al35 and the ternary alloy with gallium addition Fe65Al30Ga5 is explained in terms of the phase separation into two magnetic phases: a ferromagnetic one and a spin density wave. It is shown that the addition of boron to the initial binary alloy Fe65Al35 results in the ferromagnetic behavior of the ternary alloy.